Campfires rekindled : a forester recalls life in the Maine woods of the twenties - Kephart, George S. (Marion, Mass. : Channing Books, 1977)
in Campfire Rekindled, George Kephart describes with clarity and humor the many facets of life in backcountry Maine as experienced by him as a young forester at a time when tree harvesting called for hard, back-breaking labor from stump to mill. We see the rugged individuals who peopled those woods; the painstaking work involved in surveying and estimating yields of timberland; the miseries of bugs, of heat and of cold; the harsh primitive living conditions of pulpwood camps; the danger and drudgery of a pulpwood drive; the hazards of canoeing with a stiff-legged, 200 pound ex-linesman, the questionable delights of lunching on sandwiches that froze still in winter and, partially thawed over a campfire, became a sort of baked-Alaska". Around it all, Mr. Kephart paints a sensitve picture of the beauties of nature and the sights and sounds of the changing seasons.
Keywords: Kephart, George S; Outdoor life -- Maine -- History; Foresters -- Maine -- Biography; Lumbering -- Maine; Maine -- Social life and customs